The family Angelidae (Insecta, Mantodea) in Mexico and Central America, new records and two new synonyms - De Luna, Manuel; Hernández Baltazar, Erick; Cubillos Macías, Iker (Pensoft Publishers, 2024)
The stick-like mantis Angela miranda Saussure, 1871 (Mantodea, Angelidae) is newly recorded for the state of Chiapas in Mexico as well as for the department of Izabal in Guatemala, and the female is newly described. A re-examination of material from the Colección Nacional de Insectos (CNIN) of the Universidad Nacional Autónoma de México (UNAM) labeled as Angela miranda and recorded from Tabasco, Mexico, was conducted, revealing that they were misidentified, belonging instead to the genus Phasmomantis Saussure, 1869 (Mantidae: Stagmomantinae). Finally, Angela perpulchra Westwood, 1889 and Angela championi Saussure & Zehntner, 1894 are hereby relegated as junior synonyms of Angela miranda.